Two new species of Batrisodes Reitter (Coleoptera: Staphylinidae: Pselaphinae) from China - Jiang, Ri-Xin; Yin, Zi-Wei (Zootaxa, 2016)
Two new species, Batrisodes linyejiei Jiang and Yin, new species and Batrisodes petalosus Jiang and Yin, new species, are described from China. The former species is associated with Formica ants and the latter with Myrmica ants. A key to all 11 Batrisodes species known to occur in China is provided.